Fikih Berwawasan Dakwah - Zulkarnaini, Zulkarnaini (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
Problems of Fiqh and da’wah are often debated in society. Who actually da’wah expert is and who exactly Fiqh expert is. Fiqh expert often found preaching in various forums, such as sermons, religious speech, and so on. Otherwise, there are not a few da’wah experts who deliver kosher law, haram, makruh, mandatory, and circumcision illegal, null and forth in the middle of his talk. This could happen because of the limited power that will fill missionary activities and it is possible for public confidence to each party, especially Fiqh expert considered also able to preach or become da’wah experts. Problem that can arise in this case is whether the language of Fiqh is the same as the language of da’wah? In other words how to deliver Fiqh materials in da’wah? It means how to package the Fiqh materials clearly and decisively to be attractive, so that people are encouraged to learn and apply them in daily life, so the da’wah objectives are achieved and the provision of Fiqh not violated.